The Relationship between Mothers' Knowledge and Attitudes with the Use of IUD Contraception in the Work Area of the Lumpatan Community Health Center UPTD in 2025 - Sumastri, Heni; Novita, Nesi; Dwi Putri, Dian Anggriani (Poltekkes Kemenkes Palembang, 2025)
The use of intrauterine devices (IUDs) as a long-term contraceptive method remains low in Indonesia despite their high effectiveness and durability. Mothers' knowledge and attitudes greatly influence their decision to choose IUD contraception. This study aims to determine the relationship between mothers' knowledge and attitudes and the use of IUD contraception in the working area of the Lumpatan Community Health Center in 2025. An analytical survey with a case-control design using purposive sampling. The sample consisted of 80 respondents (40 cases of IUD users, 40 controls who were not IUD users). Data were collected using a valid and reliable questionnaire with Chi-square analysis. 62.5% of respondents had good knowledge, 52.5% had a positive attitude, and IUD use was 50%. There was a significant association between knowledge (p=0.038) and attitude (p=0.020) with IUD use. Mothers with insufficient knowledge were three times more likely not to use IUDs, and negative attitudes increased the risk of not using IUDs by 5.3 times (OR=5.286). Knowledge and attitude play a crucial role in IUD use. Education and attitude interventions for mothers are recommended to increase IUD use.